Answer:
Step-by-step explanation:
You don't specify what you're supposed to do, so I'll make an educated guess.
Given the sequence f(1) = 4, f(n) = f(n − 1) + 11, find the first 5 terms:
f(1) = 4
f(2) = f(2 - 1) + 11 = f(1) + 11 = 4 + 11 = 15
f(3) = f(2) + 11 = 15 + 11 = 26
f(4) = f(3) + 11 = 26 + 11 = 37
f(5) = 37 + 11 = 48
Answer:
you put the -3 where the x's are
Step-by-step explanation:
f(x)= -2(-3)^2 - 3(-3) + 6
i think i hope thats right
<em>The</em><em> </em><em>right</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>√</em><em>7</em><em>4</em><em> </em><em>units</em><em>.</em>
<em>Pl</em><em>ease</em><em> </em><em>see</em><em> </em><em>the</em><em> </em><em>attached</em><em> </em><em>picture</em><em> </em><em>for</em><em> full</em><em> solution</em>
<em>H</em><em>ope</em><em> it</em><em> helps</em>
<em>Good</em><em> </em><em>luck</em><em> on</em><em> your</em><em> assignment</em>
Answer:
261661bdhejejejejejdjbene Y qllwlqqlo2o1001100